Making Great Strides Yet a Learning Crisis Remains in Tanzania : Results of the SDI and SABER service Delivery Surveys - Trako, Iva; Molina, Ezequiel; Asim, Salman (World Bank, Washington, DC, 2021)
This report is organized as follows. Chapter one analyzes the emerging trends in the evolution of student’s learning outcomes in Tanzania’s primary schools and explores variations by region, ethnic-group and gender. Chapter two describes different dimensions and trends of teacher quality, such as teacher absence, content knowledge, pedagogical skills and teaching practices. Chapter three provides descriptive evidence on school governance and school management quality using the Development-World Management Survey. Chapter four presents detailed information on school inputs and infrastructure, as well as emerging trends. Chapter five provides a more general description of the different types of support available to students and their engagement to learning. Chapter six analysis the correlation between service delivery indicators and learning outcomes and provides suggestive evidence on key observable factors associated with highest gains in test scores. Chapter seven concludes by providing some clear lessons and priority areas for action.